Mapping of Themes Pertaining to Operations Management: a Refined Analysis Based on the Perceptions of Researchers, Lecturers and Practitioners - Jurandir Peinado; Alexandre Reis (BBR: Brazilian Business Review)
An article published at Revista de Gestão (REGE), an academic journal by the University of Sao Paulo, in 2013, proposed the mapping of Operations Management themes based on the editorial space provided in major journals and conf erence proceedings in the area. Based on such proposal, the current study conducted a survey to capture the importance assigned to those themes by researchers, lecturers and practitioners and how they categorized the themes into broader groupings. A factor analysis was performed with the data collected by means of the survey and several statistical tests were also carried out in order to assess the strength of the constructs and to confirm the dimensions proposed in the referred mapping of Operations Manage ment themes, allowing for its refinement. The factor analysis resulted in nine factors, seven of which very closely resemble the constructs presented in the previous paper. Thus, the results obtained herein confirm most of the previously obtained mapping, providing a further step in the discussion of the themes that are relevant to the area of Operations Management